Infection dynamics of Salmonella Infantis strains displaying different genetic backgrounds – with or without pESI-like plasmid – vary considerably - Victoria Drauch; Christian Kornschober; Nicola Palmieri; Michael Hess; Claudia Hess (Emerging Microbes and Infections)
Food-borne infections with Salmonella are among the most common causes of human diseases worldwide, and infections with the serovar Infantis are becoming increasingly important. So far, diverse phenotypes and genotypes of S. Infantis have been reported. Therefore, the present study aimed to investigate the infection dynamics of two different S. Infantis strains in broilers. For this purpose, 15 birds were infected on day 2 of life with 108 CFU/ml of a pESI+ or a pESI– S. Infantis strain, respectively. Ten uninfected birds served as in-contact birds to monitor transmission. In both groups, an increase of infection was observed from 7 days of age onwards, reaching its peak at 28 days. However, the pESI+ strain proved significantly more virulent being re-isolated from most cloacal swabs and organs by direct plating. In contrast, the pESI– strain could be re-isolated from cloacal swabs and caeca only when enrichment was applied. Although the excretion of this strain was limited, the transmission level to in-contact birds was similar to the pESI+ strain. Differences in infection dynamics were also reflected in the antibody response: whereas the pESI+ strain provoked a significant increase in antibodies, antibody levels following infection with the pESI– strain remained in the range of negative control birds. The actual findings provide for the first time evidence of S. Infantis strain-specific infectivity in broilers and confirm previous observations in the field regarding differences in persistence on farms and resistance against disinfectants.